The Regenerators, 2nd Edition : Social Criticism in Late Victorian English Canada - Cook, Ramsay (Book collections on Project MUSE., 2016)
"A crisis of faith confronted many Canadian Protestants in the late nineteenth century. With their religious beliefs challenged by the new biological sciences and historical criticism of the Bible, they turned from personal salvation to the dire social problems of the industrial age. The Regenerators explores the nature of social criticism in this era and its complex ties to the religious thinking of the day, showing how the path blazed by nineteenth-century religious liberals led not to the Kingdom of God on earth, but, ironically, to the secular city."--